Assessing cross-cultural performance: beyond just "being there", revisited. (December 2022) - Caligiuri, Paula; Sbaa, Maha Yomn; Milosevic, Mina; MacGregor-Peralta, Julia; Griffith, Richard
As a review of the literature, this paper highlights how three dimensions - task performance, skill development, and cross-cultural adjustment, have been used to understand cross-cultural performance. With respect to task performance, two criteria should be measured for all those working cross-culturally, including remote or virtual cross-cultural work: (1) how accurately employees read the unique contextual demands of a cross-cultural context and (2) how effectively they respond given the contextual and strategic demands of the task. Focusing on development of cross-cultural competencies as a performance goal we highlight the dimensions most important for assessment, focusing on self- and relationship management competencies. Regarding cross-cultural adjustment, we offer a more precise and nuanced approach which accounts for the person-environment fit in the context of working in cultural novelty.